A perspectiva da inclusão de discentes com altas habilidades/superdotação na educação superior - PEREIRA, Débora Thalita Santos (2022)
The National Policy for Special Education from the Perspective of Inclusive Education emphasizes that (BRASIL, 2008), students with high abilities/super ability show remarkable performance and high potential in any of the following aspects, isolated or combined, general intellectual ability; specific academic ability; creative or productive thinking; leadership ability; special talent for the arts and psychomotor ability. According to the legislation, this segment - part of the target audience for Special Education - needs specialized educational assistance (AEE) in order to supplement teaching and learning at all levels, stages, and modes of education. It can be seen that there is a significant number of talented people identified in the academic environment far below the projection released by the World Health Organization (WHO) - 3% to 5% - about people with high abilities/super ability (BRASIL, 2018; VIRGOLIM, 2019). There is an urgent need for changes in the educational context, given the low rates of identification of high abilities/super ability in most Higher Education Institutions and the lack or total absence of offering AEE to students identified with high potential. The driving problem of this research asks: to what extent has the process of inclusion of students with high abilities/super ability occurred at the Federal University of Maranhão - UFMA/Dom Delgado Campus? It is assumed that the University, which stands out in the state and in the country, has been exercising its educational mission with regard to training capable and competent professionals. It is believed that the Directorate of Accessibility (DACES), the sector responsible for monitoring public-target students of Special Education, enrolled in undergraduate courses in the institution, has contributed to access, permanence and successful training of these students. From this perspective, we analyze the process of inclusion of gifted students, with regard to how the identification of the same has been occurring; the teaching learning process; the AEE offered to them and their perception, and that of others involved in this study, in relation to the inclusion process in this educational institution. In the context, it was developed a research of exploratory, descriptive type, with qualitative approach, in which it was performed a survey of theoretical reference on the theme, going through basic studies such as those of Gardner (2010); Lima (2011); Renzulli (2004; 2018); Titon (2019); Virgolim (2014a; 2018), Brazilian Legislation (BRASIL, 1996; 2008; 2011; 2015; MARANHÃO, 2015), Silva et al. (2020), among others. Subsequently, we identified the conditions of inclusion of this public in the institution through the contribution of the participants of this research: the students identified or with indications of high abilities/super ability, enrolled in UFMA / Dom Delgado Campus; the teachers and coordinators of the courses of these students; and the professionals of the Directorate of Accessibility - DACES of the University. The relevance of this research is supported by the desire to carry out a differentiated pedagogical practice, in which everyone becomes an active and efficient learner and creator; in the collaboration for the growth of visibility of a social segment that is important in the construction and evolution of society, but that is socially underidentified; and in the relatively pioneering participation in the state of development of this research, by providing information and pertinent knowledge on the theme in an educational space in which there is a significant lack of research on gifted students and their education. This research offers contribution to inclusion in higher education, especially in the locus of this study, because the data collected and analyzed still reveal the obstacles in the inclusion process in the context of higher education. It was concluded, therefore, that the inclusion of students with high abilities in the Federal University of Maranhão - UFMA / Dom Delgado Campus is possible, provided that there is training of professionals of the institution about students with high abilities / overcoming challenges.